Exploring farmers' agrobiodiversity management practices and knowledge in clove agroforests of Madagascar. Issue 4 (1st July 2021) - Mariel, Juliette; Carrière, Stéphanie M.; Penot, Eric; Danthu, Pascal; Rafidison, Verohanitra; Labeyrie, Vanesse
Abstract: Interactions between farmers and agrobiodiversity are key drivers of agroecosystems sustainability and of the resilience of such systems to perturbations, but research into the human/nature interactions have overlooked some important aspects of agrobiodiversity management. In particular, farmers' ecological knowledge of the spatial organisation of plant diversity remains an open question, although knowledge and practices have major implications for the efficient and sustainable use of natural resources. Our study addresses this question by analysing how farmers spatially organise plant species in agroforests based on their knowledge of species interactions and interactions with the environment. The Analanjirofo region on the north‐east coast of Madagascar provides an interesting context to explore this issue in clove‐based agroforests, as these systems were developed by farmers as a sustainable alternative to the traditional system of shifting rice cultivation. Using an emic approach, that is based on the farmers' perspective, and participatory mapping, we studied plant diversity and its spatial organisation in 17 clove‐based agroforests and in 28 management sub‐units defined by farmers in a village of Vavatenina district. The plant functions and farmers' knowledge of plant interactions with clove tree were recorded in semi‐structured interviews, and the interactions were represented in a cognitive map. Farmers manage more than 50 plant species associated with diverse functions. Analysis of participatory maps identified four main types of species association as a function of the age of the clove trees and the associated plant diversity, and different spatial organisation patterns as a function of the topography and the surrounding species. Analysis of farmers' knowledge provided valuable insights into spatial organisation practices, how farmers perceive the adaptation of plant species to biophysical heterogeneity of the environment and whether they can be associated with other species. Our findings and methods pave the way for further interdisciplinary research on farmers/nature interactions to support the development of agrobiodiversity‐based systems taking into account farmer and scientific knowledge and practices, especially in the tropics where the expansion of cash crops in input‐intensive and mono‐cropping systems has driven major disruptions to smallholder agriculture. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Résumé: Les interactions entre les agriculteur.trice.s et l'agrobiodiversitéjouent un rôle crucial dans la durabilité des agroécosystèmes et leurrésilience. Ces interactions sont encore peu décrites et comprises. Enparticulier, les connaissances paysannes relatives à l'organisation spatialedes espèces végétales dans les systèmes complexes et diversifiés restent undomaine à explorer, d'autant qu'il est reconnu aujourd'hui que lesconnaissances et les pratiques paysannes ont des implications majeures pour uneutilisation efficace et durable des ressources naturelles. Les agroforêts à girofliers de la région d'Analanjirofo, sur la côtenord‐est de Madagascar, offrent un contexte intéressant pour explorer cettequestion car ces systèmes agroforestiers ont été développés localement parles agriculteur.trice.s comme une alternative durable au système traditionnelde la riziculture itinérante sur brûlis (tavy). Notre étude aborde cettequestion en analysant, d'une part, la diversité végétale associée auxgirofliers gérée par les agriculteur.trice.s et son organisation spatiale selonles conditions biophysiques, et d'autre part, les connaissances paysannes quisous‐tendent ces pratiques de gestion. Par une approche émique, c'est‐à‐dire reposant sur le point de vue des agriculteur.trice.s, et uneméthode de cartographie participative, nous avons étudié l'agrobiodiversitévégétale et son organisation spatiale dans 17 agroforêts à girofliers et 28sous‐unités de gestion définies par les agriculteur.trice.s au sein de leursagroforêts, dans un village du district de Vavatenina. Des entretiens semi‐structurés ont permis de documenter les usages et les fonctions desdifférentes espèces identifiées ainsi que les connaissances paysannes relativesà leurs interactions avec le giroflier. Ces connaissances ont été représentéessous la forme d'une carte cognitive. Les agriculteur.trice.s gèrent plus de 50 espèces végétales associées àdiverses fonctions au sein des agroforêts et à divers usages pour les ménages.L'analyse des cartes participatives des agroforêts a permis d'identifier quatreprincipaux types d'association d'espèces en fonction de l'âge des girofliers etde la diversité végétale associée, ainsi que différents patrons d'organisationspatiale en fonction de la topographie et des plantes environnantes. L'analysedes connaissances paysannes nous éclaire sur les fondements de ces pratiquesd'organisation, à savoir la manière dont les agriculteurs perçoiventl'adaptation des espèces à l'hétérogénéité biophysique de l'environnement et lapossibilité de les associer avec le giroflier. Nos résultats et la méthode utilisée ouvrent la voie à d'autresrecherches interdisciplinaires sur les interactions entre lesagriculteur.trice.s et la nature afin de soutenir le développement de systèmesagricoles basés sur l'agrobiodiversité et valorisant les connaissances et lespratiques paysannes, en particulier dans les régions tropicales oùl'expansion des monocultures commerciales intensives en intrants concurrencefortement l'agriculture familiale. A free Plain Language Summary can be found within the Supporting Information of this article.